Reducing pain through distraction therapy in small acute paediatric burns. Issue 7 (November 2021) - Chu, H.; Brailey, R.; Clarke, E.; Sen, S.K.
Highlights: A study of reducing distress in small acute paediatric burns, presenting to outpatient clinic, with distraction therapy. Two cohorts of patients were recruited: with and without distraction therapy. The Wong Baker TM visual analogue scale (VAS) was used to obtained pain scores at three stages of the consultation. Distraction therapy by a qualified play specialist reduces pain experienced by 23% or 2 points on the Wong Baker TM VAS. Abstract: Introduction: The majority of patients who sustained small (low % total body surface area [TBSA]) burns are assessed in an outpatient setting. This can be a traumatic experience, particularly, for paediatric patients. During the initial assessment pharmacological and non-pharmacological adjuncts, such as distraction therapy, can be employed to provide an environment that may reduce and minimise distress. In this study, we investigated whether distraction therapy reduces objective pain scores during the outpatient assessment of small acute burns in children. Methods: Two cohorts of patients were formed. In the first group (group A), the children received analgesia and routine nursing care. In the second group (group B), the children received specialist distraction therapy in addition to the same analgesia and nursing care. We recorded patient demographics, TBSA, anatomical sites and mechanism of burn. The Wong Baker™ visual analogue scale (VAS) was used to convert perceived pain, as reported by the patient or parent, into a numerical value at three set intervals during the consultation. Results: 50 patients were recruited with 32 patients in group A and 18 in group B. A larger TBSA positively correlated with higher pain scores (p < 0.05). At the start of the consultation the mean pain score without distraction therapy was 1.55 and with specialist distraction therapy was 0.33 (p < 0.05). The mean peak pain score during dressing change without distraction therapy was 6.80 and with specialist distraction was 4.47 (p < 0.05). At the end of the procedure, the mean pain score was 2.12 without distraction therapy and with specialist distraction 1.75. Conclusion: This study of pain scores in small acute paediatric burns has shown that distraction therapy provided by a qualified play specialist can reduce maximal pain by over 2 points on the Wong-Baker™ VAS. Consideration should be given to ensure that distraction therapy is available at all times during initial consultations for children who have sustained small burns.